Pendampingan Perguruan Tinggi dalam Budidaya Pertanian yang Ramah Lingkungan melalui Inovasi Teknologi TRI IN ONE_OKEY sebagai Bio Fertilizer, Bio Fungisida, dan Bio Dekomposer - Okke Rosmaladewi; Deti Rostini; Tika Purwati (LPPM UNINUS, 2024)
Extreme climate changes such as drought and attacks by plant pests (OPT) on various commodities have caused decreased production and crop failure. So far, OPT control has used chemical pesticides with high doses and intensities, which endanger consumers and pollute the environment. Indonesia is one of the three largest pesticide users in the world after Brazil and the United States. Pesticide use in Indonesia is recorded at 283 kilograms. 10.0% -12.0% of pesticides circulating in the market are illegal or fake. Indonesian society is now aware that agricultural products containing pesticide residues are very dangerous and require healthier natural agricultural products. Therefore, University Assistance both technologically and socially in Environmentally Friendly Agricultural Cultivation and Plant Protection through an Integrated OPT Control System is very important to implement. Environmentally friendly agriculture is a sustainable agricultural system that aims to increase and maintain high productivity by implementing healthy plant cultivation, paying attention to nutrient supply using organic materials, minimizing dependence on chemical fertilizers and pesticides, improving soil biota, and implementing integrated OPT control. The technological innovation implemented is using the Tri in One_okey biological control agent with the active ingredient of Trichoderma harzianum Rifai. fungus. Which is an antagonistic fungus of plant pathogens, can be used to control several plant diseases caused by phytopathogenic fungi. Because of its nature as a biofungicide, biofertilizer and biodecomposer, Tri in One_Okey can be used to protect plants from several pathogens. Increase production and improve the quality of the harvest and is safe for the environment. This innovation needs to be developed to implement environmentally friendly agriculture because Tri in One_Okey is not toxic to plants and is also a decomposer that can improve soil structure, facilitate plant root growth, retain water, increase the biological activity of beneficial soil microorganisms and is safe for the environment. So that by using Tri in One_Okey can provide benefits both ecologically, economically and socially.